THE RELEVANCE OF CONTINENTAL PHILOSOPHY OF RELIGION FOR THEOLOGY IN CONTEMPORARY SOUTH AFRICA - Anne Verhoef (Acta Theologica)
Theology in South Africa has a strong metaphysical element. This article argues the relevance of the work of modern continental philosophers of religion and theology for a post-metaphysical South African context. In their criticism of metaphysics, philosophers such as Descartes, Kant, Nietzsche, Heidegger, and Derrida raise fundamental questions about the relation between theology (including religion) and metaphysics, as well as about the future of theology and religion. Attempts to respond to these challenges by modern philosophers of religion and theology, such as Caputo, Nancy, Stoker, Kearney, and Schrijvers, are explored to identify possible approaches to theology in a post-metaphysical age. The article argues the pertinence of these insights to making theology relevant in a diverse South African society.